Determinação do potencial térmico em barras conectoras de resina acrílica autopolimerizável de fixadores externos por termografia - Krüger, Renan Marcel (2012)
The use of polymethylmethacrylate acrylic resin (PMMA) as connecting rod for external skeletal fixator (EEF) has become common in veterinary medicine due to its versatility, low cost and easy implementation. The aim of this study was to evaluate the potential of thermal damage to soft tissues and bones, by thermography, derived from the exothermic reaction during construction of connecting rod. Therefore, 18 external fixators type II were constructed by manual molding for stabilization of fractures of the radius and ulna or tibia and fibula, and were divided into four groups: simultaneous bilateral molded without irrigation (5), simultaneous bilateral molded with irrigation (4), unilateral molded without irrigation (5) and unilateral molded with irrigation (4). Through thermal imaging, from fifth to 25th minutes after mixing, temperature of PMMA acrylic rods and the pin-skin interface were determined at every minute. In a complementary study, PMMA rods measuring 150mm long by with diameters of 20mm, 25mm and 32mm were prepared with five flat intramedullary pintype, with 2, 3, 4, 5 and 6 mm diameter each. Thermal images were obtained at 30 second intervals, from the fifth to the 20th minute after mixing, and the distances at which the pins reached 50°C above the acrylic rods were measured. The maximum temperature of acrylics was 105.5ºC and irrigation provided a significant average reduction of 21.6ºC (p<0.01) in the maximum temperature, and 11.1 minutes in the permanence time above 50ºC (p<0.01). The maximum temperature of the pin-skin interface was 56.6ºC, in the four cases (22.2%) where the maximum temperature was above 50ºC the distance between acrylic and skin was between four to 6mm; through irrigation, the maximum temperature was significantly reduced by 8.1ºC (p<0.01). In conclusion, there is a potential for thermal damage when the distance from the acrylic rod where the pins touch skin was shorter than 6mm, direct irrigation is effective in reducing this potential, perform simultaneously two rods of acrylic on an type II external skeletal fixation does not alter the potential for thermal injury and, finally, it is recommended particular attention to the distance of the rod to the skin, for larger rods diameters, larger distances should be maintained to the skin, observing in this experiment the minimum distance of 4mm in rods with diameter up to 20mm, 6.5 mm in rods with diameter up to 25 mm and 10.5 mm for rods with a diameter up to 32mm.